The premeditation of catastrophe. Re-imagining Fukushima Dai-ichi - Calefati, Alessandro (Rivista Italiana di Filosofia del Linguaggio, 2023)
This article explores the concept of “premediation” and “partition of the sensible” in the context of the Fukushima disaster, one of the greatest disasters of the 21st century. The notion of premediation, coined by Richard Grusin, refers to a media device that anticipates traumatic futures, managing the subject's affectivity to prevent a “media shock”. On the other hand, the concept of partition of the sensible, introduced by Jacques Rancière, concerns the conflict over the existence and quality of a common scene and the allocation of visibility and invisibility within it. These concepts are crucial for understanding the media discourse surrounding catastrophes. Fukushima serves as a case study due to its historical and cultural significance in Japan, a country with a long history of natural and anthropogenic disasters. By examining the premediation and partitioning of the sensible in relation to Fukushima, the article explores the challenges of imagining a future community and organizing the visible and the invisible in a place burdened with the aftermath of multiple disasters. It also reflects on the temporal aspects of catastrophes, questioning the notion of events as isolated occurrences in time. The article proposes an alternative perspective influenced by Eastern traditions that view catastrophes as inherent aspects of the world, challenging the Western perception of catastrophes as ruptures in linear time. Ultimately, it seeks to reimagine the future by reconfiguring the grammar of visibility and exploring the interplay between past imaginaries and future possibilities.